PSYCHOSOCIAL CHARACTERISTICS OF WOMEN WHO COMMITTED VIOLENT CRIMES IN THE STATE OF ALCOHOL INTOXICATION - Radzevilova, Oleksandra (PSYCHOLOGICAL JOURNAL, 2017)
This article is dedicated to the issue of female criminality; namely, individual characteristics and structure of violent crimes; and study of possible predictive factors of how such behavior is formed. Today we are able to examine other aspects of female behavior: violent criminal actions, which have earlier been more typical in males. Such changes are stipulated by the fact that women have been accepting more "male" roles, including consumption of psychoactive substances. The conducted research stipulates that a significant share of aggressive crimes among females are committed in the state of alcohol intoxication and are not always directed against their closest social circle. Crimes committed in the state of alcohol intoxication are characterized exclusively by the absence of any relationships with the victim of a crime; namely, socially dangerous actions committed in the course of joint consumption of alcoholic beverages. As a result of summarizing the psychological research data and materials of criminal proceedings (conclusions of forensic examinations), comparative analysis conducted in women in regards to their characteristics allowed to pinpoint their psychosocial characteristics, peculiarities in relationships with others, the most common type of response in conflict situations, and potential influence of mentioned factors on further criminal behavior. It was established that despite the absence of statistical difference in conditions of upbringing of women (deprivation of parental care, alcoholic parents, etc.), asocial forms of behavior in the past were mainly demonstrated by women who later on committed crimes in the state of alcohol intoxication. The research cites that low level of obtained education, as established, later on reflected such characteristics in women as low level of general knowledge, underdeveloped cognitive activity, which was manifested itself in low-level demands, primitiveness, practicality and narrowness of interests. In this research, we draw attention to characteristics of the victim for the purpose of a more profound analysis of how criminal behavior is formed in females. This analysis proved that one of the predictive factors of violent actions is influence of alcohol on a person. This, along with psychosocial characteristics of females, alters perception of conflicted relationships with others, hinders prediction of far-going consequences of one's own behavior and stipulates the manner of interaction with the environment. Through studying the crime structure and social interaction of females, we have presented an opinion on a crucial affect of alcohol on the behavior during a violation of law. This is especially obvious in how impulsive the choice of weapon is during the offense as well as in post-criminal behavior of offenders.